Estudos de sólidos farmacêuticos através das técnicas de RMN no estado sólido - Oliveira, Lyege Magalhães (2014)
Approximately 80-90 % of the drugs on the market are available in solid form, sold as tablets and capsules containing product in a powdered form. A frequent problem associated to the drugs in the solid state is the low rate of dissolution, especially in aqueous medium or in polar environments. Another important feature, which is closely related to the dissolution rate, and consequently the bioavailability of the drug, is the existence of several crystalline forms that the drug can assume during the crystallization. This phenomenon is known as polymorphism and it is a serious problem for the pharmaceutical industry. Since the problem is not so simple to be characterized, it is recommended to use a number of different techniques such as XRD, Raman, IR, thermal analysis and solid state NMR, once they all have at least one limitation. In this context, this work aimed to study pharmaceutical solids by solid state NMR techniques, using matrices such as mebendazole (in polymorphic forms A and C and in commercial samples), diethylcarbamazine (in its free, citrate and maleate forms) and mycophenolic acid as well as its ester mofetil form. A set of techniques for solid state NMR based on CPMAS experiment and its variants (CP-TOSS, CP-NQS e CP-PI) were used, both observing the nucleus of carbon-13, as well as nitrogen-15. Thus, it was possible to differentiate between A and C polymorphs of mebendazole by using these techniques, and still use them in the analysis of commercial drugs. In this context, it was also possible to verify that the technique of solid state NMR can be successfully used to characterize and quantify polymorphs in absolute commercial samples. The data obtained from these analyzes demonstrated the importance of conducting an effective quality control of drugs available in the market when formulated in solid form, since it was verified that some lots sold exhibited the undesired polymorph of mebendazole. Regarding the study involving the free diethylcarbamazine and its citrate and maleate forms, NMR data were consistent and complementary to those reached by X-ray crystallography. With the use of two-dimensional FSLG-HETCOR 1H-13C experiment, it was observed the existence of intra- and intermolecular interactions through hydrogen bonds. NMR data obtained for mycophenolic acid and its ester mofetil form corroborate the structural study of this molecule, previously described in the literature only with X-ray crystallography data. The present results confirm the importance of solid state NMR in the study of pharmaceutical solids, mainly in the analysis of commercial products in Brazil, where their use should be encouraged, since this technique offers considerable advantages in the analysis of this type of product.